Promoting Peace Education by Using the Local Wisdom in Manggarai Culture, East Nusa Tenggara, Indonesia - Marselus Ruben Payong (AL-ISHLAH: Jurnal Pendidikan, 2023)
Efforts to create a culture of peace in society have been carried out in various forms, including through education in schools. However, violence still occurs in school environments, such as bullying. This study aims to explore one of the local wisdoms of the Manggarai culture, East Nusa Tenggara, Indonesia, namely go'et (poetic expression), which can be used as a medium for peace education in schools. The results show that there are many important values contained in "go’et" that can be used to promote a culture of peace for students. These values include: unity in togetherness, respect for differences, respect for others and their property, fairness to others, and love for others.